2018
DOI: 10.1007/s00401-018-1869-0
|View full text |Cite
|
Sign up to set email alerts
|

Selective targeting of 3 repeat Tau with brain penetrating single chain antibodies for the treatment of neurodegenerative disorders

Abstract: Alzheimer's disease (AD) is the most common form of dementia in the elderly affecting more than 5 million people in the U.S. AD is characterized by the accumulation of β-amyloid (Aβ) and Tau in the brain, and is manifested by severe impairments in memory and cognition. Therefore, removing tau pathology has become one of the main therapeutic goals for the treatment of AD. Tau (tubulin-associated unit) is a major neuronal cytoskeletal protein found in the CNS encoded by the gene MAPT. Alternative splicing genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 101 publications
1
12
0
Order By: Relevance
“…We have previously delivered peptides and proteins across the BBB following intraperitoneal injections when they are fused to a 38-amino acid LDL-R binding domain of ApoB (Spencer et al, 2018;Spencer et al, 2014a;Spencer et al, 2016c;Spencer et al, 2015;Spencer et al, 2014b). In contrast, experiments delivering C2-9r/siα-syn were performed following intra-venous injection (Javed et al, 2016).…”
Section: Systemically Administered Apob 11 and C2-9r Vectors Deliver mentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously delivered peptides and proteins across the BBB following intraperitoneal injections when they are fused to a 38-amino acid LDL-R binding domain of ApoB (Spencer et al, 2018;Spencer et al, 2014a;Spencer et al, 2016c;Spencer et al, 2015;Spencer et al, 2014b). In contrast, experiments delivering C2-9r/siα-syn were performed following intra-venous injection (Javed et al, 2016).…”
Section: Systemically Administered Apob 11 and C2-9r Vectors Deliver mentioning
confidence: 99%
“…In this study we have identified an alternative peptide for the transport of nucleotides across the BBB based on the apolipoprotein B (ApoB) protein targeted to the family of LDL-R (Masliah and Spencer, 2015b;Spencer and Verma, 2007). For previous studies we utilized a 38 aa peptide (Spencer et al, 2018;Spencer et al, 2014a;Spencer et al, 2016c;Spencer et al, 2015;Spencer et al, 2014b) expressed from a lentiviral vector while for the present study we used a reduced 11-amino acid sequence from the apoB protein (ApoB 11 ) protein, coupled with a 9-amino acid arginine linker for transporting siRNAs across the BBB to neuronal and glial cells following intra-peritoneal injection. We tested the effectiveness of this approach by delivering an siRNA targeting α-syn (siα-syn) into an α-syn tg mouse model of PD/DLB and showed reduced accumulation of α-syn associated with amelioration of the neurodegenerative and inflammatory pathology.…”
Section: Introductionmentioning
confidence: 99%
“…the brain in the case of neurodegenerative diseases. Addition of cell permeable peptide molecules has been shown to facilitate delivery of target molecules to intracellular locations as well as to aid in crossing the blood-brain barrier (BBB) 41,42 . Recently, cell-penetrating peptide (CPP) has also been shown to deliver cargo molecules into a variety of cell systems and across the BBB 41 .…”
Section: Cpp Allows the Transport Of Scfv Across Live Cell Membrane mentioning
confidence: 99%
“…Addition of cell permeable peptide molecules has been shown to facilitate delivery of target molecules to intracellular locations as well as to aid in crossing the blood-brain barrier (BBB) 41,42 . Recently, cell-penetrating peptide (CPP) has also been shown to deliver cargo molecules into a variety of cell systems and across the BBB 41 . We decided to use a 16-amino acid long CPP obtained from the third helix of the Antennapedia homeodomain from Drosophila in our scFv coding sequence to enable it to cross cell membranes 29,42 .…”
Section: Cpp Allows the Transport Of Scfv Across Live Cell Membrane mentioning
confidence: 99%
“…We have previously shown [ 43 ] that the AAV vectorized-scFvMC1, a recombinant version of the native anti-tau conformational mAb (monoclonal antibody) MC1, significantly reduces brain pathological tau in adult JNPL3 mice, by one-time intracranial injection. In parallel with AAV-based delivery, Spencer et al [ 44 ] have shown that systemic injection of a lentiviral vector (LV) carrying a scFv directed to 3Rtau and enhanced for brain penetration (LV-3RT-apoB) was able to reduce tau accumulation, neurodegeneration and behavioral deficit in a tau transgenic model. Although using third-generation lentiviral vectors has emerged as a promising therapeutic option for conditions as primary immunodeficiencies and cancers, it is still necessary to understand the long-term safety and efficacy of these vectors in humans, especially in respect to their potential for insertional oncogenesis [ 51 ].…”
Section: Introductionmentioning
confidence: 99%